Planar and Transparent Memristive Devices Based on Titanium Oxide Coated Silver Nanowire Networks with Tunable Switching Voltage. Issue 21 (7th April 2021) - Resende, Joao; Sekkat, Abderrahime; Nguyen, Viet Huong; Chatin, Tomy; Jiménez, Carmen; Burriel, Mónica; Bellet, Daniel; Muñoz‐Rojas, David
Abstract: Threshold switching devices are fundamental active elements in more than Moore approaches, integrating the new generation of non‐volatile memory devices. Here, the authors report an in‐plane threshold resistive switching device with an on/off ratio above 10 6, a low resistance state of 10 to 100 kΩ and a high resistance state of 10 to 100 GΩ. Our devices are based on nanocomposites of silver nanowire networks and titanium oxide, where volatile unipolar threshold switching takes place across the gap left by partially spheroidized nanowires. Device reversibility depends on the titanium oxide thickness, while nanowire network density determines the threshold voltage, which can reach as low as 0.16 V. The switching mechanism is explained through percolation between metal–semiconductor islands, in a combined tunneling conduction mechanism, followed by a Schottky emission generated via Joule heating. The devices are prepared by low‐cost, atmospheric pressure, and scalable techniques, enabling their application in printable, flexible, and transparent electronics. Abstract : The authors demonstrate a transparent resistive switching devices entirely fabricated by open‐air approaches, without a deposition chamber. The threshold voltage can be tuned by adjusting the density of AgNWs, while maintaining a high LRS/HRS ratio. They show the effect of oxide thickness on the threshold‐switching phenomenon, thus shedding light on the conduction mechanism of these types of switching devices.